FLOWERING PHENOLOGY OF MANGOSTEEN (Garcinia mangostanaL.) IN INDONESIA - Setiawan, Eko (Rekayasa, 2013)
The aim of the present study was to investigate the phenological characteristics of mangosteen and among-individual variation in flowering phenology at Bogor, Indonesia.Trees tend to flower after vegetative growth flushes and especially after dry weather. The dry period required to induce flowering in mangosteen. The fruiting season in the Bogor is from latest July to middle August. Bud stage to anthesis takes 19 days. Fruit development takes 115-140 days from anthesis. Fruits fast growth at 2-10 weeks after anthesis. After 13 weeks the growth of fruits is stop. Harvested period 44 days are from December 7 and latest in January 20. Fruits ripen over a 16-20 week period and picking is done by hand every 2-3 days. Generally, the fruits of mangosteen take 5 to 6 months to mature from fruit set. The pattern of fruit growth follows a sigmoid curve. In Bogor, mangosteen tree 25 years old, the fruit production is average of 50- 100 fruits per tree. The fruit production is depending from canopy size. The yield varies from tree to tree and from season to season.